Nephrectomy Is Not Associated with Increased Risk of Mortality or Acute Kidney Injury after High-Grade Renal Trauma: A Propensity Score Analysis of the Trauma Quality Improvement Program (TQIP). Issue 2 (22nd February 2022) - McCormick, Benjamin J.; Horns, Joshua J.; Das, Rupam; Paudel, Niraj; Hanson, Heidi A.; McCrum, Marta; Nirula, Raminder; Myers, Jeremy B.
Abstract : Purpose: Patients with high-grade renal trauma (HGRT) undergoing nephrectomy may be at higher risk for mortality compared to those treated conservatively. However, no study has controlled for degree of hemorrhage as a measure of shock. We hypothesized that after controlling for blood transfusions and other factors, nephrectomy after HGRT would be associated with increased mortality and acute kidney injury (AKI). Materials and Methods: We identified adult patients with HGRT (American Association for the Surgery of Trauma grade III–V) in TQIP (2013–2017). Propensity scoring was used to adjust for the probability of nephrectomy. Conditional logistic regression was used to analyze the association between nephrectomy and mortality and AKI. We adjusted for patient characteristics, injury specifics, and physiological factors including blood transfusions. Results: There were 12, 780 patients with HGRT, and 1, 014 (7.9%) underwent nephrectomy. Mortality was 10.6% and 4.2% in the nephrectomy and nonnephrectomy groups, respectively (p <0.001). In nephrectomy patients, 8.6% experienced AKI vs 2.4% of nonnephrectomy patients (p <0.001). In the adjusted analysis, there was no association between nephrectomy and mortality (OR=0.367, 95% CI 0.09–1.497, p=0.162). There was also no association between nephrectomy and AKI. Increasing age, nonCaucasian race, increasing Injury Severity Score, decreasing Glasgow Coma Score and blood transfusions were associated with higher mortality. For AKI, independent predictors included increasing age, male sex, and blood transfusions. Conclusions: After adjusting for volume of blood transfused in the first 24 hours, nephrectomy after HGRT was not associated with increased mortality or AKI. As a clinical principle, trauma nephrectomy should be avoided when possible.